The effects of a commercially available botanical supplement on strength, body composition, power output, and hormonal profiles in resistance-trained males - Poole, C.; Bushey, B.; Foster, C.; Campbell, B.; Willoughby, D.; Kreider, R.; Taylor, L.; Wilborn, C. (Journal of the International Society of Sports Nutrition, 2010)
Fenugreek (Trigonella foenum-graecum) is a leguminous, annual plant originating in India and North Africa. In recent years Fenugreek has been touted as an ergogenic aid. The purpose of this study was to evaluate the effects of Fenugreek supplementation on strength and body composition.